2013
DOI: 10.1158/1078-0432.ccr-12-2293
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Sorafenib and Everolimus Abrogates mTORC1 and mTORC2 Upregulation in Osteosarcoma Preclinical Models

Abstract: Purpose: The multikinase inhibitor sorafenib displays antitumor activity in preclinical models of osteosarcoma. However, in sorafenib-treated patients with metastatic-relapsed osteosarcoma, disease stabilization and tumor shrinkage were short-lived and drug resistance occurred.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(117 citation statements)
references
References 36 publications
3
109
1
4
Order By: Relevance
“…Consistently, there were no significant differences in metastatic phenotypes between SMMC-7721-CYP3A5 and SMMC-7721-GFP cells following Rictor silencing. Several published studies have demonstrated that downregulation of the mTORC2 kinase activity usually resulted from the dissociation of the mTORC2 complex (15,(34)(35)(36). More importantly, the novel finding in our current study was that CYP3A5-mediated inactivation of p-AKT (S473) resulted from the inhibition of mTORC2 kinase activity, rather than disruption of the mTORC2 complex.…”
Section: Cyp3a5-induced Intracellular Ros Enrichment Is Responsible Fsupporting
confidence: 46%
See 1 more Smart Citation
“…Consistently, there were no significant differences in metastatic phenotypes between SMMC-7721-CYP3A5 and SMMC-7721-GFP cells following Rictor silencing. Several published studies have demonstrated that downregulation of the mTORC2 kinase activity usually resulted from the dissociation of the mTORC2 complex (15,(34)(35)(36). More importantly, the novel finding in our current study was that CYP3A5-mediated inactivation of p-AKT (S473) resulted from the inhibition of mTORC2 kinase activity, rather than disruption of the mTORC2 complex.…”
Section: Cyp3a5-induced Intracellular Ros Enrichment Is Responsible Fsupporting
confidence: 46%
“…Although multiple endogenous and exogenous substances have been reported to be involved in regulation of mTORC2 activity (15,(33)(34)(35)(36)(37)(38), second messengers, for instance ROS, regulating mTORC2 remains less well understood. Structural and biochemical characterization studies conducted on TOR (the yeast ortholog of mTOR) reveal that, owing to the presence of a redox-sensitive motif, the cellular stability or functionality of TOR is redox regulated (39).…”
Section: Cyp3a5-induced Intracellular Ros Enrichment Is Responsible Fmentioning
confidence: 99%
“…Preclinical models demonstrated encouraging data of dual sorafenib and everolimus administration against this escape mechanism. 61 Therefore, combination regimen of the mTOR inhibitor everolimus and sorafenib was evaluated in patients with unresectable OS. Although 45% of the patients presented six months of progression-free survival, the target of 50% was not reached.…”
Section: Pi3k/akt/mtor Pathwaymentioning
confidence: 99%
“…Therefore, the development of more efficacious combination therapies involving SOR and other agents appears to be an attractive approach for providing improved clinical outcomes in the treatment of OS. In a recent study it was demonstrated that combination therapies of SOR and other chemotherapeutic agents may result in synergistic or additive inhibitory effects on the growth of OS cells (14).…”
Section: Introductionmentioning
confidence: 99%